PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, KOMPETENSI SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERNAL PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN - I Kadek Kumara Ari Wijaya; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2021)
Regional Government Financial Reports (LKPD) are intended to fulfill the general purpose of financial reporting and financial reports produced by local governments will later be used in decision making by the parties concerned. The purpose of this study was to examine the effect of implementing government accounting standards, human resource competence, the use of information technology, and government internal control systems on the quality of financial reports at OPD Badung Regency. The population used in this study were 3026 employees who worked in 33 OPDs in Badung Regency. Determination of the sample using purposive sampling method in order to get 99 people as the sample. After the instrument test and classical assumption test were carried out, the data analysis was then carried out using multiple linear regression analysis, determination, t test, and F test. internal government has a positive and significant effect on the quality of local government financial reports of Badung Regency.